EFFECT OF FINGOLIMOD VS. IFN-BETA1A ON NO EVIDENCE OF DISEASE ACTIVITY. Issue 11 (14th October 2015) - Silber, E; Montalban, X; Barkhof, F; Khatri, B; Hartung, HP; Ritter, S; Meier, D Piani; Tomic, D; Kappos, L
Abstract : Introduction: To compare effects of fingolimod vs. interferon beta-1a (IFN) in achieving no evidence of disease activity (NEDA-4) in patients with relapsing-remitting multiple sclerosis (RRMS) in the TRANSFORMS study. Adding Brain Volume Loss (BVL) to NEDA results in a more comprehensive and balanced measure of focal and diffuse damage. Methods: In this post-hoc analysis, we used data from the fingolimod 0.5 mg daily (n=431) and IFN 30 µg weekly (n=435) groups. NEDA-4 was defined as absence of confirmed relapses, new/enlarging T2 lesions, 6-month confirmed disability progression (CDP) and BVL (annual percent brain volume change [PBVC] of >−0.4%). 3-month CDP and additional PBVC cut-offs representing mean BVL rates in healthy adults (0.2%), MS patients (0.6%), or accelerated BVL (1.2%) were also tested. Odds ratios (OR) were calculated for differences between fingolimod- and IFN-treated groups. Results: Significantly more fingolimod (n=425) than IFN-treated patients (n=418) achieved NEDA-4 status: 27.9% vs. 16.7% (OR:1.93; 95% CI: 1.36–2.73; p=0.0002). Results were similar for other PBVC cut-offs: (>–0.2%): 20.2% vs 11.5%; 1.94; 1.30–2.90, p=0.0011; (>–0.6%): 34.6% vs 20.4%; 2.06; 1.49–2.86, p<0.0001; (>–1.2%): 40.8% vs 26.4%; 1.92; 1.42–2.60; p<0.0001. Conclusion: Fingolimod-treated patients had twice the odds of achieving NEDA-4 status over 1 year as patients treated with IFN.